APPLICATION SOCIO SCIENTIFIC ISSUES (SSI) APPROACH TO IMPROVE STUDENTS’ PHYSICS CONCEPT UNDERSTANDING ABILITY - Valen, Anissa; Sri Jumini (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
The rality that occurs in the field is that the ability to understand physics concepts is still weak. This can be seen frpm the teacher only using learning in the classroom only teaching abstract physics. Therefore, an appropriate learning method is needed so that learning objectivites can be achieved. This study aims to improve the ability to understand the concept of physics by applying the SSI approach. The research method used experiments with experimental classes and control classes as samples determined using random sampling techniques. Data analysis techniques using t-test, and N-Gain test, data processing assisted using SPSS software. The results showed that there was a difference in impoving the ability to understand the concepts of physics, namely tcount 7,40 > ttable 2,045 and hand a significant value of less than 0,05. The N-Gain Score of the experimental class is 0,74 with a high category, while the control class is 0,19 with a low category. Therefore, the application of the SSI approach can improve the ability to understand student’s physics concepts.